Toxicity effects of copper on partially-purified cholinesterase and various tissues of Clarias gariepinus (Burchell, 1822) - Padrilah, Siti Nadzirah (2017)
The contamination of Malaysian rivers is gradually increasing year by year. Various environmental issues associated with this problem have been reported with copper (Cu) being reported among the top pollutants in Malaysia especially in Mamut River, Sabah. Copper is a dangerous heavy metal with the ability to transform a continuous metal compound that can accumulate in water, causing imbalance to the biological system. Thus, fish was used as a biomarker in the present study to investigate the effects of Cu through its physical, behavioural, and biochemical changes. The study was carried out by exposing sub-lethal copper sulphate (CuSO4) concentrations (0, 0.2, 0.5, 1.0, 2.5, 5.0, 7.5, 10.0, 15.0, 20.0 mg/L) to Clarias gariepinus and observing their physical and behavioural alterations based on swimming pattern, mucus secretion, skin colour and mortality. The histopathology alterations on selected organs (gill, liver, brain, muscle and blood) were analysed under light microscope, transmission and scanning electron microscopy. It was observed that the organs of untreated group showed a normal structure of cells, while histopathological abnormalities such as vacuolation, necrotic cell, pyknotic nucleus and blebbing were observed in the treated fish as the concentration of Cu increases, which also displayed an increment in damage of the cells. In fact, enzyme activity of cholinesterase (ChE) has also found to be affected by CuSO4 in both in vivo and in vitro methods. During in vivo, ChE activity in liver and blood was mostly inhibited at 0.2 mg/L up to 41.87% and 37.1%, respectively, whereas enzyme activity was 100% inhibited at the highest concentration of 20.0 mg/L by demonstrating negative result in ChE activity. Meanwhile, ChE activity was slightly decreased in gill, brain and muscle where the enzyme was inhibited by 84.86%, 80.7% and 66.76%, respectively, at 20.0 mg/L. For in vitro study, the ChE enzyme was successfully partially-purified using affinity chromatography and procainamide sephacryl 6B as a resin. The optimum ChE activity of gills and muscle were determined at 40°C in 0.1 M Tris-HCl buffer with pH 8, while the optimum Che activity in liver and blood was in 0.1 M Tris-HCl buffer and pH 9, with optimum temperature of 30°C and 20°C respectively. However, optimum activity of ChE in brain was determined at 30°C in 0.1 M Phosphate buffer, pH 7. ChE in gills, muscle, brain and blood showed a strong affinity towards substrate acetylthiocholine iodide (ATC) while liver ChE hydrolysed butyrylthiocholine iodide (BTC) at a faster rate than other organs. Muscle has showed the lowest IC50 value at 1.968 mg/L compared to gill, liver, brain and blood with IC50 value at 1.971, 2.483, 3.358 and blood 1.975 mg/L, respectively. Therefore, the toxicology effects of Cu on the histology of selected organs have been considered as to be an alternative source for biomarker of metal toxicity, whereas the sensitivity of ChE from muscle tissues demonstrated the potential of becoming an alternative biosensor for detecting Cu.